Tools for control of the african snail (Achatina fulica, Bowdich, 1822) - Gomes, Keyla Nunes Farias; Rangel, Leonardo da Silva; Silva, Matheus Amorim Rosa e; Rocha , Leandro; Faria, Robson Xavier (Seven Editora, 2023)
The mollusk Achatina fulica, which is popularly known as the African giant snail, is the secondary vector of the helminths  Angiostrongylus cantonensis and Angiostrongylus costaricensis, both of which cause human angiostrongyliasis. This species belonging to the class Gastropoda, belongs to the subclass Pulmonata, where terrestrial mollusks such as slugs, snails and snails are inserted. The introduction of this mollusk in Brazil occurred in a disorderly manner culminating in a problem of great environmental impact due to the behavior of agglomeration, direct competition with mollusks of the natural fauna for food and space. These factors may even put the mollusks of the native fauna at risk of extinction. In addition, the fact that the mollusk does not present a food requirement makes it an imminent economic danger, due to the fact that it can devour crops, generating an economic impact. To date, the only known control measures for A. fulica are the collection and direct salinization in the mollusk. Thus, another limitation in the control of infestation of this invasive species is the ignorance of a synthetic or natural substance, with effective molluscicide action and also duly legalized by the National Health Surveillance Agency (ANVISA). In this context, it is easy to observe that there is a scarcity of studies aimed at obtaining new substances for the control of terrestrial molluscs. Since most studies of products with molluscicides are especially focused on aquatic molluscs, increasing the relevance of new studies and products, with effective action on A. fulica, and with low environmental impact. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-100